Regulation of RabGAPs involved in insulin action. (19th June 2018) - Mafakheri, Samaneh; Chadt, Alexandra; Al-Hasani, Hadi
Abstract : Rab (Ras-related proteins in brain) GTPases are key proteins responsible for a multiplicity of cellular trafficking processes. Belonging to the family of monomeric GTPases, they are regulated by cycling between their active GTP-bound and inactive GDP-bound conformations. Despite possessing a slow intrinsic GTP hydrolysis activity, Rab proteins rely on RabGAPs (Rab GTPase-activating proteins) that catalyze GTP hydrolysis and consequently inactivate the respective Rab GTPases. Two related RabGAPs, TBC1D1 and TBC1D4 (=AS160) have been described to be associated with obesity-related traits and type 2 diabetes in both mice and humans. Inactivating mutations of TBC1D1 and TBC1D4 lead to substantial changes in trafficking and subcellular distribution of the insulin-responsive glucose transporter GLUT4, and to subsequent alterations in energy substrate metabolism. The activity of the RabGAPs is controlled through complex phosphorylation events mediated by protein kinases including AKT and AMPK, and by putative regulatory interaction partners. However, the dynamics and downstream events following phosphorylation are not well understood. This review focuses on the specific role and regulation of TBC1D1 and TBC1D4 in insulin action.